The effect of a single session of plyometric training per week on fitness parameters in professional female soccer players: a randomized controlled trial - Nonnato, A.; Hulton, A. T.; Brownlee, T. E.; Beato, M. (The Journal of Strength and Conditioning Research, 2022)
As the interest and popularity of female soccer has increased over the last few decades, there still lacks research conducted with the elite population, specifically ecological training interventions during the competitive season. Therefore, the aim of this study was to compare the effectiveness of 12 weeks (undertaken once a week) of plyometric (PLY) training on physical performance in professional female soccer players during the season. Using a randomized controlled trial design, 16 players were included in the current study (mean ± SD; age 23 ± 4 years, weight 60.3 ± 4.9 kg, height 167 ± 3.7 cm) and randomized in PLY (n = 8) and Control groups (CON, n = 8), respectively. Squat jump (SJ), counter movement jump (CMJ), long jump (LJ), single-leg triple jump distance test (triple jump test), changes of direction 505 test (505-COD), and sprint 10 and 30 m were performed before and after 12 weeks of PLY training. Significant within-group differences were found in triple jump test dominant (p = 0.031, effect size [ES] = moderate) and nondominant limb (p = 0.021, ES = moderate) and sprint 10 m (p = 0.05, ES = large), whereas the CON did not report any positive variation. However, neither group reported significant variation in SJ, CMJ, LJ, 505-COD, and sprint 30 m (underlining the difficulties in obtain meaningful variation in season). These findings have strong practical applications because this study showed for the first time that a single session a week of plyometric training can significantly increase sport-specific fitness parameters in professional female soccer players during the season.